Pusat Konservasi Jalak Bali di Desa Tengkudak sebagai Upaya Mendukung Konservasi Berkelanjutan: Indonesia - Sakina Mashadi; Ni Putu Ratih Pradnyaswari Anasta Putri; Tjokorda Gede Dalem Suparsa; I Wayan Widanan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2026)
The Bali Starling (Leucopsar rothschildi) is an endemic bird species from Bali that is currently categorized as critically endangered due to habitat degradation, illegal wildlife trade, and hunting activities. Various conservation programs have been implemented, including captive breeding and habitat protection. However, the availability of integrated conservation facilities that combine breeding, research, and environmental education is still limited. Desa Tengkudak in Tabanan Regency has environmental potential and community participation that support conservation activities. This research aims to formulate the development concept of a Bali Starling Conservation Center in Desa Tengkudak to support sustainable conservation efforts. The research uses a qualitative descriptive method through field observation, literature study, and precedent studies. The results indicate that the development of a conservation center can support conservation programs through breeding facilities, rehabilitation areas, environmental education spaces, and community-based conservation activities. The architectural approach emphasizes ecological design principles that integrate buildings with the surrounding environment and minimize disturbances to the natural habitat of the birds.